2020
DOI: 10.1027/2192-0923/a000191
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fatigue on Cognitive Performance in Long-Duration Simulated Flight Missions

Abstract: Abstract. Fighter pilots may be exposed to extended flight missions. Consequently, there is increasing concern about fatigue. We investigated the effects of fatigue and cognitive performance in a simulated 11-hr mission in the 39 Gripen fighter aircraft. Five cognitive tasks were used to assess cognitive performance. Fatigue was measured with the Samn–Perelli Fatigue Index. Results showed that performance in the non-executive task degraded after approximately 7 hr. Fatigue ratings showed a matching trend to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 33 publications
2
9
0
Order By: Relevance
“…This study is part of a larger research project on psychological effects in long-duration flight missions. Hence, the methods section is in agreement with a previous publication 38 within this research project.…”
Section: Methodssupporting
confidence: 83%
See 2 more Smart Citations
“…This study is part of a larger research project on psychological effects in long-duration flight missions. Hence, the methods section is in agreement with a previous publication 38 within this research project.…”
Section: Methodssupporting
confidence: 83%
“…Regarding self-reported fatigueand as reported elsewhere 38 the Samn-Perelli Fatigue Index showed that perceived fatigue increased over time, F(5, 50) = 11.66, p < .001, p 2 = .53. Taken together, these results reveal a decrease in the positive emotional ratings addressing enthusiasm and cheerfulness and an increase in the negative emotional rating addressing boredom after approximately 7 hours into the mission.…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…Attention plays a critical role in all of these situations, implementing the selection of the sensory cues that are relevant to our ongoing purposes 1 5 while suppressing the irrelevant information the response to which has to be inhibited 6 . However, other factors independent from the goals of the task are also expected to interfere, either enhancing or degrading behavioral performance, such as fatigue 7 , 8 , motivation 6 , 9 , 10 , the degree of liberal or conservative biases in response performance 11 or intrinsic fluctuations of information coding of cognitive processes 12 . All of these factors arguably define “internal states” that highly influence perceptual outcomes under similar sensory conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Attention plays a critical role in all of these situations, implementing the selection of the sensory cues that are relevant to our ongoing purposes (Ibos et al, 2013;Moore and Armstrong, 2003;Wardak, 2006;Wardak et al, 2004Wardak et al, , 2002 while suppressing the irrelevant information the response to which has to be suppressed (Di . However, other factors independent from the goals of the task are also expected to interfere, either enhancing or degrading behavioral performance, such as fatigue (Marcora et al, 2009;Rosa et al, 2020), motivation (Brown and Bray, 2019;Di Bello et al, 2021), the degree of liberal or conservative biases in response performance (Cowley et al, 2020) or intrinsic fluctuations of information coding of cognitive processes (Gaillard et al, 2021). All of these factors arguably define "internal states" that highly influence the perceptual outcomes under similar sensory conditions.…”
Section: Introductionmentioning
confidence: 99%